Utilization of Foaming Technology in Cemented Paste Backfill of High-Mud Superfine Unclassified Tailings - Jian-wen Zhao; Xin-min Wang; Kang Peng; Shuai Li (Advances in Materials Science and Engineering)
Due to high-mud content in superfine unclassified tailings (SUT), the viscosity of cemented paste backfill (CPB) is high and its pipeline transportation properties are poor. Foaming technology was introduced to prepare a new three-phase flow backfill (TFB) using a foaming machine. Then the rheological parameters of TFB with different bubble ratio were measured and their pipeline transportation properties were simulated by Fluent. Besides, the simulation results were further verified by a semi-industrial loop test. The results indicate that the optimum ratio of TFB is a cement-sand ratio of 1 : 8, mass concentration of 70%, and bubble ratio of 20%. Compared with CPB, the decrease of bleeding rate, viscosity, and resistance loss of TFB is 27%, 25%, and 30%, respectively. Therefore, foaming technology is an innovative and feasible solution for high-mud CPB in reducing viscosity, decreasing resistance loss, and improving pipeline transporting efficiency.